Employee Hapiness dan Produktivitas: Kunci Keberhasilan Manajemen Modern - Tarida Marlin Surya; Rahayu Tri Utami; Edy Sambodja (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the effect of Employee Happiness on Employee Productivity in the context of modern management. Employee Happiness is seen as a strategic factor that influences employee work behavior, motivation, and effectiveness. This variable is measured through five main indicators, namely job satisfaction, work–life balance, coworker relationships, appreciation, and work environment. Meanwhile, employee productivity is measured based on target achievement, work quality, timeliness, and efficiency. This study uses a quantitative approach with an explanatory research method. Data were collected through a 1–5 Likert scale questionnaire and involved 120 employees as respondents. Data analysis was performed using descriptive statistics and simple linear regression to determine the extent of the influence of Employee Happiness on Employee Productivity. The results showed that employee happiness and productivity levels were in the high category. Regression analysis produced a coefficient of 0.68 with a significance value of 0.000, which means that Employee Happiness has a positive and significant effect on Employee Productivity. The coefficient of determination (R²) value of 0.47 indicates that 47% of productivity variation can be explained by employee happiness. This finding confirms that increasing Employee Happiness can be an effective strategy to drive productivity and organizational performance in a sustainable manner